The Effect of physical training on the Psychological Adjustment of stage fright of basketball athletes - Kai Ma, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Every basketball player must possess exceptional psychological qualities to perform well. This study aims to determine the impact of physical training on the psychological development of basketball players. Twenty national first-class basketball players were chosen at random to participate in this study, which collects quantitative data. Partial least square–structural equation modeling (PLS-SEM) is employed for data analysis. Based on empirical findings, the study demonstrated that physical exercise significantly affects the muscle control of athletes and enhances psychological quality indicators from multiple perspectives. This study concluded that basketball players should be strongly encouraged to engage in physical activity. When athletes in the experimental group increased their physical training, their psychological qualities improved, and they became more stable in significant competitions. This study has contributed considerable findings to both theory and practice for improving the basketball performance of athletes.